The Role of Community Health Nurses in Overcoming Dengue Hemorrhagic Fever Outbreaks in Densely Populationd Housing - Jasmin Ambas; Dwi Siyamsih; Desi Ratna Sari; Rosmaria Rosmaria; Seffiani Dwi Azmi (Oshada, 2024)
Densely populated housing often faces challenges in managing a healthy environment, which exacerbates the spread of Aedes Aegypti. Efforts to prevent Dengue Hemorrhagic Fever (DHF) can be carried out collaboratively between the community and nurses to suppress the spread of the disease. This research aims to explore the role of community nurses in dealing with dengue hemorrhagic fever outbreaks in densely populated housing areas. The research approach used in this research is a qualitative systematic literature review approach. The research results show that community nurses play an important role in empowering the community through the Larva Monitoring Officer (Jumantik) program to monitor and prevent dengue fever. Collaboration between the government, health workers and the community is very important to reduce the incidence of dengue fever significantly.